Pengaruh Jarak Antar Plat Pada Elektrokoagulasi Terhadap Pengolahan Limbah Cair Industri Kecap - Dea Kirana Nurlaili; Aussie Amalia (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The production of sweet soy sauce in Indonesia was particularly high in 2021, resulting in wastewater with elevated levels of COD, BOD and TSS. Therefore, wastewater from the soy sauce industry needs to be treated before being discharged into water bodies. In this study, the electrocoagulation method was used to reduce the levels of BOD, COD and TSS. Electrocoagulation is a process in which the anode releases active coagulants in the form of metal ions into the solution and electrolysis reactions occur, releasing hydrogen gas at the cathode. The aim of this research was to determine the effectiveness of electrocoagulation in reducing pollutants such as BOD, COD and TSS in industrial effluents. The study involved varying the distance between the electrode plates and the contact time. The treated wastewater was from a soy sauce industry in Surabaya. The results showed that increasing the electrode distance to 1cm, 2cm, 3cm and 4cm with a contact time up to 180 minutes significantly improved the efficiency of BOD, COD and TSS reduction. The best removal was achieved at 4 cm electrode distance and 180 minutes contact time, with reduction rates of 72.0% for BOD, 83.3% for COD and 90.6% for TSS.